Hyperbaric Oxygen Therapy Impact for the Function of Kidney in Metabolic Syndrome (SM) Patients - Hisnindarsyah, Hisnindarsyah (Formosa Journal of Science and Technology, 2023)
Hyperbaric Oxygen Therapy (HBOT) is the therapy of inhaling 100% pure oxygen in a hyperbaric chamber of more than 1 absolute atmosphere. Currently, the use of hyperbaric oxygen therapy is increasingly widespread, not only for decompression sickness and diving problems. But it has been used for clinical therapy, cosmetics, and geriatric care. The American Food and Drug Administration (FDA) has also confirmed various clinical indications, especially those related to metabolic syndromes such as Diabetes Mellitus (DM) and Diabetic Foot Ulcers (DFU). Then how is the use of Hyperbaric Oxygen Therapy for kidney disease? Through this literature review, it is hoped that information will be obtained regarding the effect of Hyperbaric Oxygen Therapy on kidney function, both benefits and side effects, especially in kidney disease due to metabolic syndrome (MetS).